[Subic converion ; Pinoys down under ; Jazz fiesta [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Local politicians in Olongapo threaten to delay the conversion plans of the Philippine government. A story about a group of Filipinos living and working in Melbourne, Australia. The artists of Thirdline Enterprises performed their jazz pieces at the Music Museum.